أثر كفاءة نظام بحوث التسويق في اتخاذ القرارات التسويقية (دراسة ميدانية في شركة سيريتل للاتصالات) - عبدالله, حيدر; شربجي, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يتناول البحث أثر كفاءة نظام بحوث التسويق في اتخاذ القرارات التسويقية في شركات الاتصالات السورية من خلال دراسة الأثر بين (كفاءة البيانات، كفاءة العاملين، وكفاءة البرمجيات المستخدمة في بحوث التسويق) واتخاذ القرارات التسويقية في شركات الاتصالات. اعتمد البحث على المنهج الوصفي، وشمل مجتمع البحث العاملين في قسم التسويق في شركة سيريتل للاتصالات حيث تم توزيع (70) استبانة على العاملين في مجال نظام بحوث التسويق والمسؤولين عن اتخاذ القرارات التسويقية أعيد منها (60) استبانة بنسبة استجابة بلغت (85.7%)، وباستخدام الأساليب الإحصائية المناسبة تم التوصل إلى النتائج الآتية:1- وجود علاقة طردية ذات دلالة معنوية بين كفاءة البيانات المستخدمة في نظام بحوث التسويق واتخاذ القرارات التسويقية في شركة سيريتل للإتصالات2- وجود علاقة طردية ذات دلالة معنوية بين كفاءة العاملين في نظام بحوث التسويق واتخاذ القرارات التسويقية في شركة سيريتل للإتصالات.3- وجود علاقة طردية ضعيفة ذات دلالة معنوية بين كفاءة البرمجيات المستخدمة في نظام بحوث التسويق واتخاذ القرارات التسويقية في شركة سيريتل للاتصالات.4- وجود علاقة طردية ذات دلالة معنوية بين جميع أبعاد المتغير المستقل (نظام بحوث التسويق) مع المتغير التابع (اتخاذ القرارات التسويقية) حيث بعد (كفاءة البيانات) هو البعد الأكثر تأثيراً في المتغير التابع (اتخاذ القرارات التسويقية) وبعد (كفاءة البرمجيات) هو البعد الأقل تأثيراً في المتغير التابع.This paper deals with the impact of the Efficiency of marketing research system in making marketing decisions in the Syrian telecommunications companies, by studying the impact of (Data efficiency and workers efficiency and software efficiency that used in marketing research system) and making marketing decisions in telecommunications companies. The research adopted the descriptive approach, which included the research community who working in Syriatel Telecom were distributed (70) to identify the workers in the marketing research field and responsible for making marketing decisions, (60) questionnaire was responded, in rate (85.7%), by using appropriate statistical methods the study reached the following results:1- There is a significant positive correlation between the efficiency of the used data in marketing research system and making marketing decisions in Syriatel Telecom.2- There is a positive relationship and significant morale among the workers efficiency in marketing research system and making marketing decisions in Syriatel Telecom.3- There is a positive relationship and weak significant differences between the efficiency of the software which used in marketing research system and make marketing decisions in Syriatel Telecom.4- There is a significant positive relationship among all the independent variables (efficiency of marketing research system) with the dependent variable (making marketing decisions) where the variable (data efficiency) is the most influential dimension in the dependent variable (making marketing decisions) and the variable (Software efficiency) is the lower influent dimension in the dependent variable (making marketing decisions).